Target‐controlled propofol infusion with or without bispectral index monitoring of sedation during advanced gastrointestinal endoscopy - Lin, Yueh‐Juh; Wang, Yi‐Chia; Huang, Hui‐Hsun; Huang, Chi‐Hsiang; Liao, Min‐Xiu; Lin, Pei‐Lin (Journal of gastroenterology and hepatology, 2020)
Background and Aim Target‐controlled infusion (TCI) uses averaged pharmacokinetic datasets derived from population samples to automatically control the infusion rate. Bispectral index (BIS) technology non‐invasively measures levels of consciousness during surgical procedures. We compared the efficacy and safety of propofol TCI with or without BIS monitoring for sedation during advanced gastrointestinal endoscopy. Methods This prospective study enrolled 200 patients who were premedicated with midazolam 2 mg and alfentanil 0.4 mg before undergoing advanced gastrointestinal endoscopy. The initial target blood concentration of propofol was set at 1.0 μg/mL, and adjustments of 0.2 μg/mL were made as necessary to maintain moderate‐to‐deep sedation. Patients were randomized to either the BIS‐blind group and evaluated for depth of anesthesia by monitoring scores of 1–2 on the Modified Observer's Assessment of Alertness/Sedation scale (n = 100) or to the BIS‐open group and monitored by BIS scores of 60–80 (n = 100). The primary outcome was the total amount of propofol required to maintain anesthesia. Secondary outcomes were sedation‐induced adverse events, recovery, and quality of sedation (endoscopist and patient satisfaction). Results The mean propofol infusion rate was significantly higher in patients not monitored by BIS scores than in those who were (5.44 ± 2.12 vs 4.76 ± 1.84 mg/kg/h; P = 0.016). Levels of satisfaction were higher for endoscopists who used BIS monitoring than in those who did not. Conclusions Mean infusion rates were higher in propofol TCI without BIS monitoring compared with propofol TCI with BIS during advanced gastrointestinal endoscopy. Endoscopists expressed satisfaction with BIS monitoring.